Peran Ayah dalam Praktik Menyusui - Lisma Evareny, Mohammad Hakimi, Retna Siwi Padmawati (Fakultas Kedokteran Universitas Gadjah Mada, 2010)
Background: In Indonesia the prevalence of exclusive breastfeeding in 2007 was 32%. Although breastfeeding is a common practice, exclusive breastfeeding remains unpracticed optimally due to some influential factors. One factor to be considered here is father’s role. However, until recently studies regarding father’s role in breastfeeding practice have not been fully explored in Indonesia. In Bukittinggi exclusive breastfeeding rate was 63,5% in 2008.Objective: To investigate the relationship between the father’s role and breastfeeding practices in Bukittinggi Municipality.Method: This was an observational study with cross-sectional study design. Subjects were families with babies aged 0 – 6 months using non probability sampling. The independent variable was the father’s role and the dependent variable was breastfeeding practices. Meanwhile, the extraneous variables included knowledge, attitude, mother’s occupation; father’s working hours in a day, and income. The data were analyzed using univariable analysis, bivariable analysis with chi-square test, and multivariable analysis with logistic regression.Results: The result of multivariable analysis showed that there was a significant relationship between the father’s role and breastfeeding practice, by including father’s knowledge, mother’s knowledge, father’s attitude and mother’s attitude that could predict by 12% (RP= 1.93; 95% CI= 1.36 – 2.74).Conclusion: The prevalence of exclusive breastfeeding practices in the supporting father group was greater than in the group that non-supporting father. The recommendations are that fathers should be targeted audience in the breastfeeding promotion.Keywords: father’s role, breastfeeding practices